PENGARUH PIJAT AKUPRESURE DALAM MENGURANGI STRES BELAJAR SISWA - Istiqomah Dwi Andari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2023)
A response or feeling that is not comfortable experienced by someone who is influenced by individuals and external situations that cause special psychological and physiological consequences for someone. The purpose of this study was to determine whether there was an effect of acupressure massage in reducing student learning stress. This study used a quantitative method using a quasy experimental design, a non-equivalent control design with pre and post tests. The population of high school students who experience learning stress with the characteristics of dizziness, feeling tired quickly, taking samples with an accident sampling system. The sample of this study were 60 student respondents with 30 intervention group respondents and 30 control groups. Data analysis used Wilcoxon and Mann Whitney. The results of this study were based on the results of the analysis of students who experienced learning stress had lower scores compared to before the acupressure massage was carried out. The results of the analysis test using Man Whitney showed a P value of 0.000, meaning that there was an effect of acupressure massage in overcoming learning stress in high school student. Keywords: Acupressure, Learning Stress